Intrinsic Network Brain Dysfunction Correlates With Temporal Complexity in Generalized Anxiety Disorder and Panic Disorder - Xu, Li; Xu, Huazhen; Ding, Huachen; Li, Jinyang; Wang, Chun (Frontiers in Human Neuroscience, 2021)
Background Previous studies have taken a whole-brain perspective on generalized anxiety disorder (GAD) and panic disorder (PD) in the assumption that intrinsic fluctuations throughout the entire scan are static. However, it has recently been suggested that dynamic alternations in functional connectivity may reflect changes in macroscopic neural activity patterns underlying critical aspects of cognition and behavior, and thus may act as biomarkers of disease. Methods In this study, resting state fMRI data were collected from 26 generalized anxiety disorder patients, 22 panic disorder patients, and 26 healthy controls. We investigated dynamic functional connectivity (dFNC) by using group spatial independent component analysis, a sliding window approach, and k-means clustering methods. For group comparisons, temporal properties of dFNC states were statistically analysed. Results Dynamic analysis demonstrated two discrete connectivity ‘States’ across the entire group: a more segregated State I, and a strongly integrated State II. Compared to healthy controls, patients with anxiety disorder spent more time in the weakly within-network State I, while conducted fewer transitions and dwelled shorter in the integrated State II. Additionally, analysis of dFNC strength showed that connections associated with anxiety disorders were identified including regions belonging to default mode (DM), executive control (EC) and salience (SA) networks, especially the connections between SAN and DMN network. Conclusion More common but less specific alterations were detected in GAD and PD groups, which implied that they might have similar state-dependent neurophysiological mechanisms, and what’s more, could hopefully help us better understand their abnormal affective and cognitive performance in clinic.